Watching murder: ISIS, death videos and radicalization - Cottee, Simon (Routledge, 2022)
Why We Watch -- Horror and Hysteria -- Curators and Enthusiasts -- Documenters and Cleaners -- Normies -- The Poltergeist Theory of Terrorism.